A Review on Non-invasive Respiratory Support for Management of Respiratory Distress in Extremely Preterm Infants - Shi, Yuan; Muniraman, Hemananda; Biniwale, Manoj; Ramanathan, Rangasamy (Frontiers in Pediatrics, 2020)
Majority of extremely preterm infants require positive pressure ventilatory support at the time of delivery or during the transitional period. Most of these infants present with respiratory distress (RD) and continue to require significant respiratory support in the neonatal intensive care unit (NICU). Bronchopulmonary dysplasia (BPD) remains as one of the major morbidities among survivors of the extremely preterm infants. BPD is associated with long-term adverse pulmonary and neurological outcomes. Invasive mechanical ventilation (IMV) and supplemental oxygen are two major risk factors for the development of BPD. Noninvasive ventilation (NIV) has been shown to decrease the need for IMV and reduce the risk of BPD when compared to IMV. This article reviews respiratory management with current NIV support strategies in extremely preterm infants both in delivery room as well as in the NICU and discusses the evidence to support commonly used NIV modes including nasal continuous positive airway pressure (NCPAP), nasal intermittent positive pressure ventilation (NIPPV), bi-level positive pressure (BI-PAP), high flow nasal cannula (HFNC) and newer NIV strategies currently being studied including, nasal high frequency ventilation (NHFV) and noninvasive neutrally adjusted ventilatory assist (NIV-NAVA). Randomized, clinical trials have shown that early NIPPV is superior to NCPAP to decrease the need for intubation and IMV in preterm infants with RD. It is also important to understand that selection of the device used to deliver NIPPV has a significant impact on its success. Ventilator generated NIPPV results in significantly lower rates of extubation failures when compared to Bi-PAP. Future studies should address synchronized NIPPV including NIV-NAVA and early rescue use of NHFV in the respiratory management of extremely preterm infants.